A case report of life-threatening acute dysphagia in dermatomyositis: Challenges in diagnosis and treatment. Issue 17 (April 2018) - Kwon, Kyoung Min; Lee, Jung Soo; Kim, Yeo Hyung
Abstract: Rationale: Although dysphagia is a known complication of dermatomyositis, sudden onset of dysphagia without the notable aggravation of other symptoms can make the diagnosis and treatment challenging. Patient concerns: A 53-year-old male diagnosed as dermatomyositis 1 month ago came to our emergency department complaining of a sudden inability to swallow solid foods and liquids. The patient showed generalized edema, but the muscle power was not different compared with 1 month ago. Diagnoses: Serum creatine kinase level was lower than that measured 2 weeks ago. Computed tomography scan of the larynx, chest, abdomen, and pelvis, an esophagogastroduodenoscopy, and brain magnetic resonance imaging were unremarkable. A videofluoroscopic swallowing study revealed inadequate pharyngeal contraction and slightly decreased upper esophageal sphincter opening with silent aspiration. Intervention: Treatment with oral prednisolone, intravenous methylprednisolone, azathioprine, and intravenous immunoglobulins was applied. During the course of medical treatment for life-threatening dysphagia, he continued with rehabilitative therapy. Outcomes: He could swallow saliva at 2 months and showed normal swallowing function at 3 months from the onset of dysphagia. Dysphagia has not recurred for 3 years after recovery. Lessons: A multidisciplinary approach is necessary to diagnose severe acute dysphagia due to exacerbation of underlying dermatomyositis rather than other structural or neurological causes. Appropriate supportive care is important because dysphagia can be life-threatening and last for a long time.